Synthesis of single-crystal-like nanoporous carbon membranes and their application in overall water splitting - Hong Wang (Nature Portfolio, 2017)
Hierarchical, nanoporous graphitic membranes are synthetically challenging yet attractive materials, due to their structural integrity. Here, the authors fabricate freestanding, porous carbon membranes with single-crystal-like graphitic order which serve as water splitting electrocatalysts upon cobalt doping.